2016
DOI: 10.7554/elife.11627
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the transcription factor Meis1 prevents sympathetic neurons target-field innervation and increases susceptibility to sudden cardiac death

Abstract: Although cardio-vascular incidents and sudden cardiac death (SCD) are among the leading causes of premature death in the general population, the origins remain unidentified in many cases. Genome-wide association studies have identified Meis1 as a risk factor for SCD. We report that Meis1 inactivation in the mouse neural crest leads to an altered sympatho-vagal regulation of cardiac rhythmicity in adults characterized by a chronotropic incompetence and cardiac conduction defects, thus increasing the susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 143 publications
7
45
0
Order By: Relevance
“…Experimental evidences converged to promote dopaminergic neurons of the hypothalamic A11 nucleus as a strong candidate likely involved in the promotion of PLMS and sympathetic activity 44 . Meis1 is widely expressed in the nervous system 7 9 10 and recent Magnetic Resonance Imaging studies of whole brain functional connectivity in RLS patients demonstrated alterations in cortical and subcortical network, suggesting potential involvement of cortical, subcortical, spinal and peripheral nervous areas 45 . We recently showed that during mouse sympathetic neurons development, Meis1 serves as a dedicated maintenance factor allowing correct innervation of target organs and Meis1 inactivation lead to altered retrograde transport 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidences converged to promote dopaminergic neurons of the hypothalamic A11 nucleus as a strong candidate likely involved in the promotion of PLMS and sympathetic activity 44 . Meis1 is widely expressed in the nervous system 7 9 10 and recent Magnetic Resonance Imaging studies of whole brain functional connectivity in RLS patients demonstrated alterations in cortical and subcortical network, suggesting potential involvement of cortical, subcortical, spinal and peripheral nervous areas 45 . We recently showed that during mouse sympathetic neurons development, Meis1 serves as a dedicated maintenance factor allowing correct innervation of target organs and Meis1 inactivation lead to altered retrograde transport 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, MEIS1 , a gene coding for a transcription factor of the TALE (Three Amino acid Loop Extension) Homeodomain family, is the largest risk factor identified so far 3 4 5 . In various species, Meis1 has been implicated in the development of several peripheral organs and nervous system structures including the striatum, the retina, the forebrain, the cerebellum and sympathetic neurons 6 7 8 9 10 . The SNPs (Single-Nucleotide Polymorphisms) identified in the eighth intron of the MEIS1 gene suggest that deregulations of mRNA transcription and/or processing participate in the etiology of RLS.…”
mentioning
confidence: 99%
“…We now look at the co-factors in detail. MEIS1 is a homeobox encoding TF, known to be crucial for neuronal differentiation [ 37 ]. REST has been shown to repress MEIS1 expression in non-neuronal cells via recruitment of Polycomb Repressor Complexes [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Then, HRV was evaluated by power spectral analysis (ms 2 ) using the fast Fourier transformation (segment length of 2048 beats, linear interpolation with resampling to a 20 Hz interbeat time series and Hamming windowing). The cutoff frequency ranges for the LFr powers (HFr: 1.5-5 Hz) were chosen according to those used in the literature (106).…”
Section: Methodsmentioning
confidence: 99%